Accelerating carbon neutrality could help China's energy system align with below 1.5 °C. (1st July 2023) - Ma, Xueqing; Peng, Tianduo; Zhang, Yanru; Wang, Lining; Pan, Xunzhang
Abstract: To support the achievement of the Paris Agreement's 1.5 °C global warming threshold, China aims to peak CO2 emissions before 2030 and achieve carbon neutrality before 2060. However, the specific carbon neutrality pathway remains to be designed. By applying a refined Chinese version of Global Change Analysis Model, this study examines implications of four illustrative carbon neutrality scenarios for aligning China's energy system with below 1.5 °C by 2100. The results feature a trade-off between China's ambition to transform its energy system toward mid-century and its reliance on carbon dioxide removal (CDR) after carbon neutrality. From a full time perspective until 2100, accelerating carbon neutrality could help China's energy system align with below 1.5 °C. Compared to a 2060 carbon neutrality scenario, a 2050 carbon neutrality scenario reduces China's total mitigation costs between 2021 and 2100 by 1.04% of GDP, reduces reliance on CDR by 36%, and provides some additional co-benefits, such as reduced air pollutants. However, special attention needs to be paid to the fact that accelerating carbon neutrality poses greater challenges and costs to China in overcoming development inertia and restructuring its energy system over the next 30–40 years. Compared to a 2060 carbon neutrality scenario, a 2050 scenario increases China's mitigation costs by a factor of 1.13 between 2021 and 2050. This study suggests through quantitative evidence that China could accelerate emissions reductions and energy system transformation to achieve carbon neutrality, based on its national circumstances and capabilities and international support. Highlights: Implication of carbon neutrality for China's energy system under 1.5 °C is explored. Four illustrative carbon neutrality scenarios are assessed by integrated modelling. Trade-off between energy transition to mid-century and reliance on CDR is shown. AcCelerating carbon neutrality reduces China's mitigation costs to align with 1.5 °C. China could consider accelerating transition and pursuing early carbon neutrality.